Role of the neutrophil-lymphocyte relationship in the prognostic value for exacerbation and mortality among patients with Chronic Obstructive Pulmonary Disease: integrative literature review (Research, Society and Development, 2021)
COPD is a disease characterized by airflow restriction, systemic inflammation and periods of acute exacerbation. Recently, the neutrophil-lymphocyte ratio (RNL) has been shown to be a sensitive predictor of acute exacerbation and the prognosis of patients with COPD. The aim of this study was to discuss the compliance between NRL in the exacerbation of COPD, presenting information that correlates the leukocyte alteration with the worsening of symptoms and the outcome of patients with COPD. Thus, an integrative literature review was carried out in the PubMed database of productions from the last 10 years. The descriptors used were: “Neutrophil to Lymphocyte Ratio”, “Chronic Obstructive Pulmonary Disease” and “Acute Exacerbation”, which were combined to delimit the search. Ten articles were selected at the end of the searches, with the years 2015, 2018 and 2020 being the most prevalent, with 20% of the publications each. The studies originated in Turkey, responsible for 40% of them, 30% of the publications were carried out in China, and Iran, Israel and Japan, each country with 10%. Higher NRL levels were found in patients who had in-hospital death (≥ 4) and hospital admission (≥ 2.7). However, some studies have shown that NRL is not useful in determining the eosinophilic phenotype of exacerbated COPD, and that inflammatory markers rise distinctly according to the endotype of exacerbation. Therefore, NRL is a simple and cost-effective parameter for prediction, monitoring and prognosis of acute exacerbation of COPD, including in stable patients, showing a positive association between acute exacerbation and cellular relationships in patients with COPD.